ANALISIS REGRESI PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP KINERJA DOSEN UNIVERSITAS INDO GLOBAL MANDIRI PALEMBANG - Siti Komariah Hildayanti (Universitas Indo Global Mandiri)
Job satisfaction and work motivation of lecturers are the two factors that influence the lecturers performance. This study aimed to analyze: (a) the effect of job satisfaction on the lecturer performance, (b) the effect of work motivation on the lecturer performance, (c) the simultaneous effect between job satisfaction and motivation on the lecturers performance. This research is a descriptive study that describing job satisfaction, motivation, and performance of the UIGM Palembanglecturers. The approach used in this study is quantitative. The population are all of lecturers at UIGM Palembang which have characteristics: (1) Permanent lecturer, (2) Stay in Palembang, and (3) Implement Tri Dharma Perguruan Tinggi. The sampling technique in this research is done by proportional random sampling. The entire population consist of 132 permanent lecturers spread across five faculties and one master program. The samples were taken some 40% of 132 is 52.8 rounded to 53.There are two independent variables and one dependent variable. The independent variables that affect, include work motivation (X1) and job satisfaction (X2). The dependent variable is the variable that is affected, in this case the lecturer performance (Y). Type of instrument used to collect data from the field was in the form of a questionnaire with closed questions and readily available alternative answer used Likert Scale. For testing the validity of data was implemented the validity and reliability test. Prerequisite test analysis using multicolinierity, heteroscedasticity, normality and linearity test. Data analyst was using analysts descriptions, simple regression and multiple regression test. The calculations were using SPSS 20 windows 2007.Testing the hypothesis I resulted generate the regression equation Y = 0.901 + 0.431 X1. The regression coefficient for the variable job satisfaction was 0.431, t-test value 2.059 and p-value of 0.045. This means with 95% confidence, it can be stated that if the motivation to work held constant, job satisfaction effect on the lecturers performance significantly and positively. This shows that higher perception of lecturers satisfaction, the performance lecturers will be higher. Vice versa, the lower of the lecturer satisfaction, lecturer performance will be lower too.Testing the hypothesis II resulted in the regression equation Y = 0.901 + 0.454 X2. The regression coefficient for the work motivation variable was 0.454, t-test value 2.719 and p-value 0.009. This means with 95% confidence, it can be stated that if the job satisfaction is considered fixed, the work motivation effect on the lecturers performance positively and significantly. This shows that the higher the perception of lecturer about work motivation, the higher of the lecturers performance. Conversely, the lower of the lecturer motivation, then the lower of performance lecturer.Based on the multiple regression analysis of the effect of job satisfaction and work motivation on lecturer performance resulted in the regression equation Y = 0.901 + 0.431 X1 + 0.454 X2 means the hypothesis that simultaneous job satisfaction and work motivation influence on the lecturers performance. The R2 = 0.236 means that the contribution of job satisfaction and motivation on the UIGM lecturer performance at 23.6%, while the remaining 66.4% influenced by other variables outside. Thus the higher motivation and lecturer job satisfaction, the lecturers performance will be higher as well, and vice versa.Improved lecturers performance can be optimized when there are salary increases, support funding in research and dedication to the community, keeping in touch, comfort, creation of healthy competition, fairly performance appraisal, giving opportunity to participate in scientific activities with financing from UIGM, and encourage lecturers to continue their education to a higher level. In addition, the lecturer needs to continue to be motivated to carry out research, and community service as their each field at a cost of foundations or grants from the Direktorat Jenderal Pendidikan Tinggi. Keywords : Work Motivation, Job Satisfaction, Lecturer Performance, Simple Regression Analysis, Multiple Regression Analysis.